The Effect of Organizational Culture on Implementation of Accounting Information Systems with the Mediating Role of Types of Capital - Sadeq Hassoon Mozan Moza; Mahdi Moradi; Mahdi Salehi (Iranian Journal of Accounting, Auditing & Finance)
This paper primarily investigates the pivotal role of organizational culture in implementing accounting information systems. The study also explores the mediating role of various types of capital, including intellectual, social, human, and spiritual capital. The collected data are analyzed through a questionnaire. 191 participants have completed questionnaires. SPSS, Stata, and SmartPLS software are used for data analysis, and hypotheses are checked using various statistical methods. The results showed that organizational culture is a factor in improving the implementation of accounting information systems. Intellectual, human, and spiritual capital mediates the relationship between organizational culture and implementation, but social capital does not influence this relationship. This study has investigated the effect of organizational culture on the implementation of accounting information systems. The findings, which underscore the importance of intellectual, human, and spiritual capital in mediating this relationship, while social capital was found to have no influence, provide a robust foundation for further research and practical applications in the field. This research provides valuable insights into the complex interplay between organizational culture, capital types and the implementation of accounting information systems, reassuring the academic community of the soundness of the research.